Capillary electrophoresis as a tool for genotyping SH3 mediated coffee leaf rust resistance - Gutiérrez Calle, Savina Alejandra; Sánchez Díaz, Rosa A.; Delgado Silva, Yolanda Bedsabé; Montenegro, Juan D.; Gutiérrez Reynoso, Dina Lida; Maicelo Quintana, Jorge Luis; Guerrero Abad, Juan Carlos (Universidad Nacional de Trujillo, 2021)
9 Páginas